A method to include reservoir operations in catchment hydrological models using SHETRAN. (April 2021) - Hughes, Daryl; Birkinshaw, Stephen; Parkin, Geoff
Abstract : Reservoir construction and operation have significant impacts on catchment hydrology, flood risk and fluvial processes. However, few available hydrological modelling packages can simulate complex, dynamic, manually-operated reservoir control structures. We present SHETRAN-Reservoir, a physically-based spatially distributed modelling tool to simulate catchment hydrology, including reservoir operations. We also propose a method for deriving parsimonious reservoir operation rules from real-world observations. Application of SHETRAN-Reservoir to the Upper Cocker catchment in the Lake District National Park, UK, is shown to improve modelling of hydrological response. Modelling combined climate change and water resource management scenarios demonstrates the influence of operational control rules on hydrological impacts, especially during droughts. We discuss how SHETRAN-Reservoir can be applied to other reservoir-containing catchments to guide decisions concerning water resources, ecology and flood risk. We also discuss potential future software developments. Highlights: Manual reservoir operations should be modelled in dam-containing catchments. Parsimonious reservoir operation rules can be derived from hydrometric data. The newly developed SHETRAN-Reservoir software simulates reservoir operations. Our methods improve model outputs for Crummock Water in the UK Lake District. This approach supports sustainable water resource management under climate change.